Which One Is The Most Important In Bank: Liquidity Or Capital Resiliency? - Fatwa Aulia; Dwi Nastiti Danarsari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to examine the fulfillment of the Liquidity Coverage Ratio (LCR) and Capital Adequacy Ratio (CAR) of banks towards bank credit growth in Indonesia. The researchers included macroeconomic factors (GDP and BI Rate) as control variables and bank size (core capital category) to support the research testing. The influence of LCR and CAR on bank credit growth with KBMI categories 2, 3, and 4 during quarterly periods (Q4 2018 - Q2 2023) is tested using multiple linear regression. The study findings indicate that banks that enhance liquidity management by increasing the LCR can lead to a reduction in credit distribution. However, the CAR does not have a major influence on credit growth. This is because bank capital in Indonesia is very robust. The relationship between the LCR and credit growth in all KBMI categories is not significantly influenced by the core capital category of banks. In addition, the KBMI has a little impact on the correlation between CAR and credit growth in KBMI banks 2 and 3, but it does have a moderating effect on KBMI 4 banks